Evaluation of analgesic effect of hydroalcoholic extract of cardamom fruit in male rat - Habibian, Leyla; Zargarnezhad, Marjan; Ahmadi, Rahim; Sadat Ghamgyn Meraj, Mohadeseh (Journal of Biological Studies, 2022)
Due to the significance of pain management and the adverse effects of synthetic analgesic drugs, the use of herbal medicine for pain relief has gained popularity worldwide. This study investigated the analgesic effects of hydroalcoholic extract of cardamom fruit in male rats. In this experimental-laboratory study, male Wistar rats were divided into 7 groups (6 rats in each group): the control group (treated with normal saline) and the groups treated with 100, 200 and 400 mg/kg of hydroalcoholic extract of cardamom fruit, control group receiving morphine (1 mg/kg), control group receiving naloxone (2 mg/kg), and a group receiving “naloxone (2 mg/kg) + extract (200 mg/kg)”. Tail flick and writhing tests were used to evaluate the analgesic effects of the extract. Data were analyzed using one-way ANOVA. 200 and 400 mg/kg of hydroalcoholic extract of cardamom fruit significantly reduced pain level compared to the control group in the tail flick test and all three doses of the extract (100, 200 and 400 mg/kg) significantly reduced pain level in the writhing test. From the results, it can be concluded that the hydroalcoholic extract of green cardamom fruit has analgesic effects and can reduce the sensation of pain caused by central and environmental factors. The use of green cardamom extract as an analgesic substance can be considered by researchers in the clinical field.